The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1540-6261.2007.01257.x
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance and Firm Value: The Impact of the 2002 Governance Rules

Abstract: The 2001 to 2002 corporate scandals led to the Sarbanes–Oxley Act and to various amendments to the U.S. stock exchanges' regulations. We find that the announcement of these rules has a significant effect on firm value. Firms that are less compliant with the provisions of the rules earn positive abnormal returns compared to firms that are more compliant. We also find variation in the response across firm size. Large firms that are less compliant earn positive abnormal returns but small firms that are less compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
334
2
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 584 publications
(363 citation statements)
references
References 43 publications
25
334
2
2
Order By: Relevance
“…As mentioned by Chhaochharia and Grinstein (2007) and Wintoki (2007), these studies suffered from identification problems -i.e., these studies identified different key dates and news items; hence their interpretation differed as to whether the U.S. SOX was likely to pass. The Japanese case provides a favorable opportunity to avoid such identification problems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As mentioned by Chhaochharia and Grinstein (2007) and Wintoki (2007), these studies suffered from identification problems -i.e., these studies identified different key dates and news items; hence their interpretation differed as to whether the U.S. SOX was likely to pass. The Japanese case provides a favorable opportunity to avoid such identification problems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although effective governance may ultimately lead to more satisfied shareholders, it is costly. For example, the organizational experience with the Sarbanes-Oxley Act (2002) has shown that (a) governmental regulations may become necessary because opportunistic managers are exceedingly reluctant to implement voluntary governance reforms that benefit shareholders and (b) the costs of good corporate governance can be very high (Chhaochharia & Grinstein, 2007;Zhang, 2007). Other evidence indicates that these costs are unlikely to be counterbalanced by improved organizational performance.…”
Section: The Prevalence Of Macrolevel Factors For Shareholder-orientementioning
confidence: 99%
“…Rezaee and Jain (2006) and Zhang (2007) fi nd mixed results in their study of the aggregate US stock-market reaction to passage of the act. Chhaochharia and Grinstein (2007) compare the abnormal returns of a portfolio of fi rms that were already compliant with the act's provisions before its passage to those that were not. They fi nd a 6-20 percent abnormal return, suggesting net benefi ts to shareholders.…”
Section: Sarbanes-oxley Act and Other Securities Lawsmentioning
confidence: 99%